2016
DOI: 10.3390/s16121984
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Performance Instability in Piezoresistive Sensors: Inducement and Improvement

Abstract: The field of piezoresistive sensors has been undergoing a significant revolution in terms of design methodology, material technology and micromachining process. However, the temperature dependence of sensor characteristics remains a hurdle to cross. This review focuses on the issues in thermal-performance instability of piezoresistive sensors. Based on the operation fundamental, inducements to the instability are investigated in detail and correspondingly available ameliorative methods are presented. Pros and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 120 publications
1
22
0
Order By: Relevance
“…Piezoresistive pressure sensors have been reported to exhibit thermal dependency similar to that reported by Liu et al [19]. Thermal dependence can have its source either in the Si itself or in the elements used to package the SE.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Piezoresistive pressure sensors have been reported to exhibit thermal dependency similar to that reported by Liu et al [19]. Thermal dependence can have its source either in the Si itself or in the elements used to package the SE.…”
Section: Introductionsupporting
confidence: 63%
“…This mechanism has been widely studied over the last 50 years, where the mechanical properties of single crystal Si [5][6][7] and its piezoresistive properties at different doping concentrations [8][9][10][11][12] have been well established. Enhanced models, which account for both the anisotropy of Si and thermal effects on the piezoresistivity, have also been recently published [13][14][15][16][17][18][19]. This provides an excellent basis for initial sensor design, but cannot be solely relied upon to accurately predict the output of a complete pressure sensor.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed the decrease in drain current by almost 2 μA for 25 °C temperature difference. This behavior is related to the temperature dependence of the transistors threshold voltage, mobility of the charge carriers as well as the piezoresistive coefficients . This dependence affects the sensor sensitivity and limits its accuracy for changes in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The output voltage difference is plotted against applied pressure and for different temperatures between 0 and 75 °C. Quarter bridges deliver almost 50% of the sensitivity of the half bridges as it is shown when the output voltage difference of bridge 1 compared to bridge 2 and bridge 3 to bridge 4 respectively. When Figure (a) compared to (b) it is observed that the physical aspect ratio W/L of the reference transistors influences the stress sensitivity of the bridge as well.…”
Section: Resultsmentioning
confidence: 99%
“…The resistances of the piezoresistors will be changed by these stresses according to [ 22 ]: where is the piezoresistive coefficient with p-type silicon. The relationship between and can be given as [ 22 , 23 ]. …”
Section: Working Principle and Methodologymentioning
confidence: 99%